2016
DOI: 10.1080/10255842.2016.1182631
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical interactions of different mini-plate fixations and maxilla advancements in the Le Fort I Osteotomy: a finite element analysis

Abstract: This study investigates the biomechanical interaction of different mini-plate fixation types (shapes/sizes and patterns) with segmental advancement levels on the Le Fort I osteotomy using the non-linear finite element (FE) approach. Nine models were generated under a standard 1-piece LeFort I osteotomy for advancement with 3, 6 and 9 mm distances and four mini-plates with three fixation patterns including LL, LI, and II patterns placed on the maxillae models by integrating computed tomography images and comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 29 publications
4
10
0
Order By: Relevance
“…Therefore, future research should have at least a 1-year follow-up and should distinguish osteosyntheses with plates and screws vs. only screws to assess the symptomatic device removal rate appropriately. The mandible is exposed to considerably higher biomechanical forces compared to the maxilla [70,71]. Higher forces acting on the mandible may lead to loosening of screws and, thereafter, to inflammation especially in osteotomies because, unlike fractures, there is no interfragmentary stability [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, future research should have at least a 1-year follow-up and should distinguish osteosyntheses with plates and screws vs. only screws to assess the symptomatic device removal rate appropriately. The mandible is exposed to considerably higher biomechanical forces compared to the maxilla [70,71]. Higher forces acting on the mandible may lead to loosening of screws and, thereafter, to inflammation especially in osteotomies because, unlike fractures, there is no interfragmentary stability [2].…”
Section: Discussionmentioning
confidence: 99%
“…The mandible is exposed to considerably higher biomechanical forces compared to the maxilla [ 70 , 71 ]. Higher forces acting on the mandible may lead to loosening of screws and, thereafter, to inflammation especially in osteotomies because, unlike fractures, there is no interfragmentary stability [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The masticatory forces after mandibular reconstructions ranged from 28 to 186 N [ 166 ]. However, the mechanical stress surrounding osteosynthesis systems is multi-factorial and is affected by the location of the fracture [ 1 ], differences in interfragmentary stability [ 1 ], mandibular height [ 1 ], degree and direction of movement [ 167 ], and preoperative masticatory forces [ 159 , 168 , 169 ]. Load-sharing osteosynthesis allows sharing of the load between bone segments and the osteosynthesis system (e.g., fractures with interfragmentary stability) whereas in load-bearing osteosynthesis, the complete load at the fracture site is carried by the osteosynthesis system without interfragmentary stability [ 1 , 170 ].…”
Section: Pre-clinical Evidencementioning
confidence: 99%
“…Huang et al found that L-shaped mini-plates with lateral fixation provide better stability. However, the risk for mini-plate fracture increases when maxillary advancement is larger than 5 mm [ 9 ]. As the traditional titanium mini-plates demand contouring to fit maxillary geometry profiles for each individual patient, it may affect the accuracy of placement [ 10 ].…”
Section: Introductionmentioning
confidence: 99%